A new Anurida Laboulbène species from China with mitochondrial genome and DNA barcode analyses (Collembola, Neanuridae, Pseudachorutinae) - Gao, Yan; Godeiro, Nerivania Nunes; Bu, Yun (Zootaxa, 2026)
A new species, Anurida huangxiei sp. nov., discovered from the bank of the Huangpu River in Shanghai, East China, is described and illustrated. It is characterized by the special reticulations on the body, the absence of ocelli, 18–22 elliptical vesicles on PAO, six blunt sensilla with distinct heel and trilobed apical vesicle on Ant. IV, seta p3 in front of p2–p4 line on thoracic segments II and III, seta p2 present on Abd. I–IV, and slender sensilla on dorsal side. In addition, the complete mitochondrial genome of the new species was sequenced and analyzed. Its COI barcode was also compared with other 19 species of the subfamily Pseudachorutinae and the genetic distances between them were calculated.